An evaluation of the water and sanitation programme as implemented through the Mvula Trust by the Limpopo Department of Education - Swanepoel, Pieter L. (Department of Civil Engineering, 2019)
The study evaluates the water and sanitation programme as implemented through The Mvula Trust by the Limpopo Department of Education (LDoE) in terms of the agency agreement between the two parties, thereby providing: • A precedent of public services and infrastructure delivery through co-production • A precedent of sustainability innovation in the midst of resource scarcity through the large-scale decentralisation of basic services with off-grid water and sanitation systems. The study looks into the context in which the formal arrangement between The Mvula Trust and the LDoE came into place and which continues to be implemented as an alternative means of public service delivery by the state. It further looks into the extent of the deliverables of the programme, which consists of more than 1 843 projects, and on which more than a billion rand has been spent. The scope of works for most of the projects implemented by The Mvula Trust consist mainly of the provisioning and upgrading of water and sanitation services at public schools in the province, including the construction of the dry waste sanitation facilities and the drilling of boreholes. This decentralised form of basic service delivery, unconnected to municipal water supply or sewer systems, was borne mostly out of necessity, but is an improvement on the unsustainable and unaffordable centralised water supply and sewer systems that have been found to be both unsustainable and unaffordable in the long run. The scale and consistency of the roll-out of decentralised water and sanitation systems by the LDoE is commendable and has made it the norm, rather than the exception at schools in the province. The expenditure on a portion of the programme, that is mostly completed, is evaluated to determine the success or failures of the programme as measured against the cost parameter, and finds that The Mvula Trust managed to complete the overall programme within budget. However, when the data for each addendum is compared, it becomes evident that only three of the eight addendums were completed within budget, four was less than 20% over the budget and one was more than 20% over the budget. When the expenditure data per project is evaluated, it reveals that only 62% of the projects can be deemed to be successful in terms of the cost parameter of projects that finished within the allocated project cost. However, the trendline suggests that The Mvula Trust is increasingly improving in keeping their expenditure within the allocated budget. The study reveals that The Mvula Trust is remunerated 10% of the project cost as an implementing agent management fee, with an additional 2% for disbursements. This management fee percentage is fairly high when compared to other implementing agents, especially when the fees for Professional Service Providers are added, which combined with the management fee result in more than 30% of the construction cost. An evaluation of this capital expenditure at these facilities reveals that there is a substantial difference between the average expenditure per learner depending on the size of the school as measured by the school enrolment in 2017. For primary schools the capital expenditure amounts to R6,818 per learner at micro primary schools, with enrolments of less than 135 learners; as opposed to R1,230 per learner at mega primary schools, with enrolments of more than 931 learners. Similarly, for secondary schools the capital expenditure amounts to R6,242 per learner at micro secondary schools, with enrolments of less than 200 learners; as opposed to R1,387 per learner at mega secondary schools, with enrolments of more than 1 000 learners. With the substantial infrastructure needs that exist at schools in Limpopo, coupled with limited funding to address these challenges, it would be prudent for expenditure to be channelled to where it would have the greatest impact. The data would suggest that the greatest impact would be achieved if priority is given to the implementation of infrastructure projects at larger sized schools.